Stomach Content in Relation to Spawning and Population Characteristics of Acetes Serrulatus Kroyer (Decapoda: Sergestidae) in the Coastal Waters of Pontian, Malaysia - Oh, Siew Yong (2011)
Marine shrimps of genus Acetes Milne-Edwards, 1980 are ecologically and commercially important. Systematic studies on Acetes in Malaysia indicate that Acetes serrulatus was the most abundant species in Johor waters. Thus, the biology and population dynamics of A. serrulatus from coastal waters of Pontian, Johor, Peninsular Malaysia during April 2008 to April 2009 was specifically investigated. The results showed that the mean total length and total weight was 20.53 ± 0.04 mm and 43.03 ± 0.23 mg respectively for males while 22.82 ± 0.04 mm and 61.47 ± 0.36 mg were recorded for the females. Significant differences were observed between mean total length of males and females as well as annual size frequency distributions (p < 0.05). The relationship between total length and total weight of A. serrulatus was W = 0.0098 TL2.7706 (r2= 0.83) for males and W = 0.0073 TL2.8846 (r2 = 0.82) for females. Negative allometric nature of growth (b < 3, p < 0.05) was observed. Acetes serrulatus is omnivorous and feed on phytoplankton, zooplankton and microcrustaceans. Majority of the stomach sacs examined (88.72%) were filled up with food while only 11.28% were empty. The overall sex ratio was found to be 1:1.4 (male:female). Based on the monthly ovary maturation, A. serrulatus is a continuous spawner with peak breeding activities during June - July and December in agreement with changes in the Gonadosomatic Index (GSI) value. The asymptotic length (L) and growth coefficient (K) was estimated as 28.35 mm and 1.75 yr-1 for males while 29.40 mm and 1.50 yr-1 for females. The growth performance index () was estimated at 3.13 with maximum life span (tmax) of 1.86 year. The recruitment pattern was continuous throughout the year. Higher total mortality (Z) rate was observed in males (Z = 5.27 yr-1) than females (Z = 4.97 yr-1). Fishing mortality (F) for males was 2.66 yr-1 while 2.63 yr-1 for females. Natural mortality (M) was estimated at 2.61 yr-1 and 2.34 yr-1 for males and females, respectively. The exploitation rate (E) of 0.52 indicated that the stock of A. serrulatus was exploited. This Acetes research warrants greater attention for better management of the resources and effective conservation measures for their sustainability.